The walking dead: Blender as a tool for paleontologists with a case study on extinct arachnids. (July 2014) - Garwood, Russell; Dunlop, Jason
Abstract : This paper serves two roles. First, it acts as an introduction to Blender, an open-source computer graphics program, which can be of utility to paleontologists. To lessen the software's otherwise steep learning curve, a step-by-step guide to create an idealized reconstruction of a fossil in the form of a three-dimensional model in Blender, or to use the software to render results from 'virtual paleontology' techniques, is provided as an online supplemental data file. Second, here we demonstrate the use of Blender with a case study on the extinct trigonotarbid arachnids. We report the limb articulations of members of the Devonian genus Palaeocharinus on the basis of exceptionally preserved fossils from the Rhynie Cherts of Scotland. We use these newly reported articulations to create a Blender model, and draw comparisons with the gait of extant arachnids to produce as accurate a representation of the trigonotarbid flexing its limbs and walking as possible, presented in additional online supplemental data files. Knowledge of the limb articulations of trigonotarbid arachnids also allows us to discuss their functional morphology: trigonotarbids' limbs and gait were likely comparable to extant cursorial spiders, but lacked some innovations seen in more derived arachnids.